The golden age of retirement - Line Smart Bakken (University of Oslo, Department of Economics, 2006)
The aim of this paper is to investigate income, saving and consumption for households around retirement age. When doing this, there are different objectives which can be analyzed. First of all it is possible to get some insight of welfare of elderly when they reach retirement. Second, it is interesting to check the predictions of the life-cycle model by investigating consumption trends of households. Register data files are used to construct households which are used in the analysis throughout the paper. Modeling was done for a particular group of Norwegian households who were tracked through their retirement transition period. For each household there are characterizations such as pension income, labor income, wealth accumulation, saving and consumption. The results show that the households increase their after tax income and consumption, and have a high level of net financial wealth. In addition is a connection between high income replacement ratio and low income before retirement found. Households who have high income replacement ratios increase consumption more than households with low income replacement. The results also suggest that retirement decisions are independent of other decision making such as consumption and saving.
Keywords: E21; 330; Life-cycle model; pension income; households; income replacement; retirement behavior; Ältere Arbeitskräfte; Altersgrenze; Haushaltseinkommen; Sparen; Lebenszyklus; Norwegen